THE DIALOGUE OF LANGUAGES AND CULTURES IN BASQUE PLACE NAMES - OLGA S. Chesnokova; PEDRO LEONARDO Talavera-Ibarra (Ибероамериканские тетради, 2016)
Presently, Basque toponymy comes out as the result of a dialogue between cultures and languages inside the original territory of Basqueland, as well as the result of a dialogue with the regions historically tied to Euskadi. The toponymy also includes Basque names in other lands, a presence that bears witness to a Basque expansion. This feature allows us to apply to the entire corpus of Basque toponymy a methodology that estab-lishes its dialogic and associative ties as well as its semiotic parameters. In view of the agglutinative character of the Basque language, it is possible to clearly define, from a historic perspective, the topoformative elements and their limits. Nowadays, on the other hand, an important characteristic of Basque toponymy is the pres-ence of duplicate names, a process explained by both an official policy and the standardization and revival of Basque language and literature.